Antifungal mechanism of cell-free supernatant produced by Trichoderma virens and its efficacy for the control of pear Valsa canker - Zhang, Yang; Lu, Ying; Jin, Zhaoyang; Li, Bo; Wu, Li; He, Yujian (Frontiers in Microbiology, 2024)
Pear Valsa canker caused by Valsa pyri (V. pyri) is a severe fungal disease that poses a major threat to pear production. The present study aimed to assess the effectiveness of cell-free supernatant (CFS) produced by Trichoderma virens (T. virens) in the prevention of the development of pear Valsa canker and reveal the inhibitory mechanism against the pathogenic fungi. Using morphological characteristics and phylogenetic analysis, the pathogen was identified as V. pyri G1H, and the biocontrol fungus was identified as T. virens WJ561. CFS derived from WJ561 exhibited strong inhibition of mycelial growth and was confirmed to be capable of reducing the pathogenicity of V. pyri on pear leaves and twigs. Scanning electron microscopy showed that the CFS caused mycelial deformation and shrinkage. The CFS also destroyed hyphal membranes, leading to the leakage of cellular contents. Further analysis revealed that the CFS effectively suppressed V. pyri growth in large part through the downregulation of the expression of antioxidant defenses-related genes and affecting the enzymatic detoxification pathways of reactive oxygen species (ROS) in this pathogen that culminated in the excessive ROS accumulation, consequently leading to hyphal oxidative damage of V. pyri. Artesunate was identified as the major practical component of CFS by liquid chromatograph-mass spectrometry (LC-MS) and had antifungal activity on V. pyri. In conclusion, this study lays the groundwork for the utilization of T. virens to control V. pyri in practical production.